2016
DOI: 10.13044/j.sdewes.2016.04.0011
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Selected Water Quality Parameters on Flow Rates in River Profiles in the Czech Republic

Abstract: The paper analyses dependence of water quality parameters on flow rates at several sites in the Vltava River catchment in the Czech Republic. The presented results indicate that at the monitored sites, concentrations of nitrates, suspended solids and dissolved oxygen are in direct relation to flow rate. Temperature has an inverse relationship to flow rate. Other parameters show various relationships to flow rate at individual monitored sites or do not show any statistically significant relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Analysis showed that the concentrations increase with the increase of water flow but the dependence between them is nonlinear. Such behavior is typical for diffuse pollution of nitrogen [2,21]. …”
Section: Resultsmentioning
confidence: 89%
“…Analysis showed that the concentrations increase with the increase of water flow but the dependence between them is nonlinear. Such behavior is typical for diffuse pollution of nitrogen [2,21]. …”
Section: Resultsmentioning
confidence: 89%
“…Studies have even found elevated concentrations of uranium in plants and cattle occurring in the area [36]. The river has only deteriorated further due to the decrease in flow with the recent drought in South Africa, Hanslik et al [37] indicated that in the presence of point source pollution decreased flow often results in increased eutrophication, algal blooms and decreased dissolved oxygen. Despite its degraded condition it is still utilised by both the people of Bekkersdal [38] and as a tourist site for recreational and professional angling [39].…”
Section: Use Of the Wonderfonteinspruit (Inclusive Of Donaldson Dam)mentioning
confidence: 99%
“…For instance, in [21], the interactions between DO and flow in the river Waihou catchment, New Zealand, were evaluated with the purpose of supplying minimum flow and flow variability requirements for instream ecology, in order to provide a more holistic framework for defining flow requirements in the catchment area. In [22], the relationship between some water quality parameters, including DO, and flow rates at several sites in the Vltava River catchment in the Czech Republic were evaluated. The results indicated that concentrations of nitrates, suspended solids, and dissolved oxygen are in direct relation to flow rate.…”
Section: Introductionmentioning
confidence: 99%